Managment of construction joint ventures - Goh, Nai Kiew. (2008)
It is evident that the recession had hit the construction industry, as the volume of construction works at home is not enough to support the optimum growth of the industry. Thus contractors have to venture overseas to secure contracts to utilise the excess capacity and other competitive advantages not available domestically. This has prompted many contractors to look to joint ventures as a competitive means of entering the overseas market.